A Survey on Oral Cancer Analysis among Hospitalized Patients Based Bioinformatics - Shruthi, G; Madhusudhanan, J (International Journal of Computer Sciences and Engineering, 2025)
Recent technologies and developments on bioinformatics emphasize for analysis of the biological data which is generated by the biological sciences and biotechnology. Definition of Bioinformatics is used to storage, manipulation and interpretation data of nucleic acids and amino acids and molecular rules and system that affects the structure. Cancer is a major and serious public health problem worldwide. Cancer is uncontrolled proliferation of cells that arise from virtually any cell type in the body. This paper discusses about the cancer symptoms, analysis and the preventing measures. However, additionally, there are even more discussion about oral cancer among hospitalized patients. This paper discusses the levels of preventing oral cancers and characteristics of patients is directed to get a better understanding of the existing research problems in this emerging field